Characteristics of geopolymer hybrid concrete in peat water. (October 2019) - Wijaya, M F; Olivia, M; Wibisono, G; Saputra, E; Wang, S
Abstract: Geopolymer hybrid is a combination of geopolymer and Ordinary Portland Cement (OPC) or other binders to produce an alternative binder. This type of binder could be used to transform low-quality fly ash into multi-purpose concrete. Ordinary Portland Cement (OPC) concrete subjected to an acidic organic environment such as peatland, is more prone to deterioration in long-term than concrete using the supplementary cementitious material. In this research, the geopolymer was made by activating low-quality fly ash (contains more than 5% carbon) with the alkaline activator. The inclusion of OPC and Portland Cement Composite (PCC) as a fly ash replacement material is intended to promote curing at ambient temperature and immobilization of heavy metals in fly ash. The specimens were cast and cured at ambient temperature up to 28 days. OPC was used as a control mix. Subsequently, the concrete was immersed in fresh peat water in the laboratory up to 28 days. Characteristics of the geopolymer hybrid such as compressive strength, porosity, and leaching were determined. Microstructure analysis, such as SEM-EDX and FTIR, were conducted. Results show that the geopolymer hybrid has a good strength development at early days. At 28 days, there was a reduction of strength and increase of porosity, probably due to the attack of calcium from the OPC concrete. There was a transformation of aluminosilicate gel into C/N-A-S-H that is advantageous for the strength development at the early days. However, a weaker material has formed in the long term that cannot resist further acid attack. It can be concluded that the geopolymer hybrid is a promising binder, but it is essential to design the material appropriately to have better strength, durability and environmental properties in the long term.